Age‐specific incidence rates and risk factors for respiratory syncytial virus‐associated lower respiratory tract illness in cohort children under 5 years old in the Philippines. Issue 4 (19th March 2019) - Ueno, Fumihiko; Tamaki, Raita; Saito, Mayuko; Okamoto, Michiko; Saito‐Obata, Mariko; Kamigaki, Taro; Suzuki, Akira; Segubre‐Mercado, Edelwisa; Aloyon, Hananiah D.; Tallo, Veronica; Lupisan, Socorro P.; Oshitani, Hitoshi; et al.
Abstract : Background: Respiratory syncytial virus (RSV) is one of the main viral causes of lower respiratory tract illness (LRTI), especially in young children. RSV vaccines, including maternal and infant vaccines, are under development; however, more epidemiological studies are needed to develop effective vaccination strategies. Objectives: To estimate detailed age‐specific incidence rates and severity of RSV‐associated LRTI (RSV‐LRTI) using data from a community‐based prospective cohort study in the Philippines. Patients/Methods: Cohort children who visited health facilities due to acute respiratory symptoms were identified, and nasopharyngeal swabs were collected to detect RSV. The severity of RSV‐LRTI was assessed using the severity definition proposed by the World Health Organization. Risk factors for developing RSV‐LRTI and contribution of SpO2 measurement were also evaluated. Results: A total of 395 RSV episodes which occurred in children aged 2‐59 months were categorised as 183 RSV‐LRTI, 72 as severe RSV‐LRTI and 29 as very severe RSV‐LRTI. Children aged 3‐5 months had the highest incidence rate of RSV‐LRTI, at 207.4 per 1000 child‐years (95% CI: 149.0‐279.5). Younger age group, place of living and low educational level of caregivers were associated with developing RSV‐LRTI. Clinical manifestations had low levels of agreement with hypoxaemia as measured by pulse oximeter. Conclusion: The highest burden of RSV was observed in young infants aged 3‐5 months, whereas the burden was also high in those aged 12‐20 months. Future vaccination strategies should consider the protection of older children, especially those aged one year, as well as young infants.